EVALUATION OF RADIOACTIVE EQUILIBRIUM STATES OF RADIONUCLIDESA IN THE URANIUM DECAY CHAIN (Web of Technology: Multidimensional Research Journal, 2025)
This article investigayes the factors that cause disturbances in radioactive equilibrium with in the uranium decay chain. Numerous nuclear-physical factors influence the violation of radioactive equilibrium, the most significant of which is the heat energy released by the multiple radioisotopes formed from the parent ore. Additionally, relationships among atomic mass number, half-life, decay energy, radioactive equilibrium coefficient and nuclear decay constants of radionuclides in the uranium decay chain are analyzed.